Pelatihan Pengelolaan Sdm Untuk Meningkatkan Kualitas Umkm Dalam Produktivitas Penjualan - Rismawati; Purwanti; Anshor, Abdul Halim; Maulana, Donny; Huda, Miftahul (SABA JAYA PUBLISHER, 2025)
Pelatihan